Transplant or dialysis: What’s the better choice for RCC-induced ESRD patients? A 20-year analysis of OPTN/UNOS data - Hao, Xiaowei; Lai, Wenhui; Xia, Xinze; Xu, Junnan; Wu, Yangyang; Lv, Chao; Lv, Kaikai; Huang, Shuai; Luo, Zhenjun; Meng, Qingyang; Yuan, Qing; Dong, Jun (Frontiers in Oncology, 2022)
Purpose: The incidence of end-stage renal disease (ESRD) caused by renal cell carcinoma (RCC) is increasing with the high prevalence of RCC as well as those with treatment-related renal function impairment. Worries about tumor recurrence after transplant-related immunosuppression hinder the recommendation of kidney transplantation for RCC-induced ESRD patients. However, no direct analysis has been performed to identify whether kidney transplantation can offer better survival than maintaining dialysis. Materials and Methods: This retrospective population-based cohort study was based on Organ Procurement and Transplantation Network data released in March 2021. Characteristics and outcomes were compared, including patient and graft survival of candidates and recipients with RCC-induced ESRD etiology as well as other primary diseases. Results: Patients with RCC-induced ESRD were older; more likely to be male, White, and obese; and more likely to have a history of diabetes and dialysis. They also had higher creatinine levels, more delayed graft function, more primary non-function, and higher Kidney Donor Profile Index scores donor, compared with the glomerulonephritis group (GN). While waiting, RCC candidates suffered the worst outcomes of all groups, a 44% (adjusted hazard ratio [aHR], 1.44 [1.27–1.62]) higher risk of removal than GN patients. After transplantation, RCC recipients demonstrated comparable patient survival and better graft survival (p=0.21, p=0.13, respectively). Compared with still waiting RCC patients, RCC recipients who received kidney transplants had significantly better outcomes (13.6 [9.3–17.8] vs. 61 [52–68.4] %), decreasing the death or deteriorating risk by 84% (aHR, 0.16 [0.13–0.20]). Conclusions: Patients with RCC-induced ESRD can dramatically benefit from kidney transplantation. Hence, these patients should not be limited to transplantation by strict strategies or a delayed waiting time out of their malignancy history.